2019
DOI: 10.1111/sms.13371
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive cardiovascular disease risk profile in patients with schizophrenia

Abstract: Patients with schizophrenia are physically inactive and have high prevalence of cardiovascular disease (CVD). Peak oxygen uptake (V̇O2peak) is one of the strongest predictors for CVD, yet is rarely investigated in this patient population, and how V̇O2peak relates to other conventional CVD risk measures in this population is unclear. We measured treadmill V̇O2peak along with daily physical activity assessed by triaxial accelerometry, body mass index (BMI), waist circumference, blood pressure, lipid profiles, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Tables and , 38 studies met criteria for inclusion in the qualitative synthesis and all were published after 2005 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite methodological limitations across studies, descriptive synthesis of findings indicated that suboptimal CRF was observed in Stage 0 (offspring), Stage 1 (CHR/UHR), and Stage 2 (FEP) including evidence from incidence studies and case–control comparisons . Likewise, impaired CRF was reported in clinical samples classified as Stage 3 or 4 compared with matched HC . Many case–control studies matched groups for demographic variables known to influence CRF but not for BMI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite increasing evidence of consumers’ poor physical health and efforts to prevent morbidity (Baxter et al ; Furness et al ; Hughes et al ), their mortality age is disproportionately younger compared with the general population (Correll et al ; Nemani et al ). Recognized co‐occurring physical health conditions for consumers include poor cardiovascular (Brobakken et al ), respiratory (Jørgensen et al ), and cardiometabolic (Yoca et al ) health. Lifestyle behaviours such as sub‐optimal dental hygiene (Wey et al ), unsafe sexual practices (Montejo et al ), substance misuse (Libuy et al ), and harmful diet (Firth et al ) are also linked with consumers’ premature mortality.…”
Section: Introductionmentioning
confidence: 99%